Scholar‐built collections: A study of user requirements for research in large‐scale digital libraries. Issue 1 (2014) - Fenlon, Katrina; Senseney, Megan; Green, Harriett; Bhattacharyya, Sayan; Willis, Craig; Downie, J. S.
ABSTRACT: To realize the great potential value of large‐scale digital libraries, we need a fuller understanding of the range of ways in which scholarly communities conduct research, or want to conduct research within them. Scholars build collections in the course of their work. How can we anticipate and support various kinds of collection‐building and ‐use, in order to support the diversity of researchers who work in libraries of digital books? This paper reports selected results of a study of how potential user groups of the HathiTrust Digital Library create and use collections in their research. This study aims to contribute to our broader understanding of scholarly practice, particularly of humanities scholars' collecting activities. The results of the study inform ongoing work to develop a workset‐creation tool for the HathiTrust Research Center.